Habitual residence as a forum of international judicial jurisdiction in some sectors of international family law - Sabido Rodríguez, Mercedes (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Habitual residence as a criterion for attributing international jurisdiction has undoubted advantages as it is a factual and realistic connection, but it also derives important disadvantages derived, at the European level, from the absence of a single and uniform concept. Having verified this reality on the basis of Spanish judicial practice, and after analyzing the work carried out by the Court of Justice on the delimitation of this concept, we question the need to establish a single and uniform concept of habitual residence that addresses all cases and facilitates the determination of the court with international jurisdiction to hear disputes relating to matrimonial crises and other related measures and those relating to parental responsibility, economic regimes and maintenance obligations.
Keywords: habitual residence; international jurisdiction; marriage crisis; parental responsibility; maintenance obligations; matrimonial property regime